Comparative efficacy of interventional therapy with or without targeted immunotherapy in Child-Pugh B hepatocellular carcinoma patients: a single-center, retrospective study - Guo, Xu-Wei; Zhao, Man; Duan, Xiao-Ling; Han, Guang-Jie; Wang, Jin-Feng; Shi, Jian-Fei; Han, Xin; Yin, Fei; Yang, Guang (Frontiers in Oncology, 2025)
BackgroundCurrent large clinical trials mainly focus on Child-Pugh A (CP-A) stage hepatocellular carcinoma (HCC) patients, with limited data on CP-B patients especially those classified as B8-9, whose treatment needs remain inadequately addressed. This study aims to evaluate the safety efficacy of interventional treatments, with or without targeted-immunotherapy and characteristics of CP-B stage HCC patients receiving.MethodsThis single-center retrospective investigation incorporated 119 patients were stratified into two cohorts: the interventional therapy cohort (42) and the combined targeted immunotherapy cohort (77). The clinical data, overall survival (OS), progression-free survival (PFS), and therapeutic efficacy of both groups were meticulously recorded and comprehensively analyzed. Survival disparities were statistically compared employing the Kaplan-Meier survival analysis method and the log-rank test. Tumor remission was appraised in accordance with the RECIST 1.1 and mRECIST criteria. Independent influencing factors were discerned through multifactorial COX regression analysis. Subsequently, survival prediction models were constructed to generate column line graphs, and the safety profiles and adverse events associated with diverse treatment modalities were also evaluated.Results119 patients with CP-B grade HCC were included, and the median survival (mOS) of patients who received combination therapy was 21.4 months (vs 13.2, P=0.038) superior to that of interventional therapy, and the median progression-free survival (mPFS) of 12.7 months (vs 10.9 months, P=0.183) was not significantly improved. The OS of patients in group B7 who received combination therapy was 24.6 months (vs 11.9, P=0.006) was superior to that of the intervention, while there was no significant improvement in patients in groups B8-9. The objective remission rate (ORR) was higher in the combination therapy than in the intervention group (RECIST: 32.5% vs 11.9%, P = 0.014; mRECIST: 48.1% vs 23.8%, P = 0.010). Except for Child-Pugh score progression (P = 0.003), there was no significant difference in the occurrence of all-grade and ≥grade 3 adverse events in the combination therapy group compared with the intervention group (P > 0.05).ConclusionInterventional therapy combined with targeted and immunotherapy can be a safe and effective treatment for patients with Child-Pugh grade B hepatocellular carcinoma in the setting of controlled liver function impairment.